Análise das variáveis discretas e de séries temporais da cinemática da marcha de mulheres com dor femoropatelar - Ayres, Isabella Guimarães Tinoco (2020)
Introduction: Patellofemoral pain (PFP) is a clinical condition considered of multifactorial etiology and its causes are still not well known. Objectives: 1. Compare angular and linear kinematics, time and maximum, minimum values and range of motion (ROM) in the gait support phase, in women with and without PFP. 2. Compare possible differences in angular kinematics during the gait cycle in women with and without PFP, using the Statistic Parametric Mapping (SPM). Methods: Cross-sectional study that evaluated the kinematics of 236 women with DFP and 161 women in control group (CG) during gait. Results: 1. Women with PFP have less time in double initial and terminal support, less time in the entire support phase, and more time in simple support, compared to CG. Women with PFP have a difference in the angular parameters of the gait compared to asymptomatic women. 2. A difference was found in the kinematics of women with PFP compared to the CG. Conclusion: 1. Despite the differences found in some angular parameters, the variables had no or small size of the effect, however, as it is a task often like walking, the differences found may have a significant impact over the years. 2. The frontal plane concentrates the biggest difference in the kinematics of women with PFP compared to the CG.